DIMENSI KOSMOLOGIS GEDUNG PUSAT (BALAIRUNG) UNIVERSITAS GADJAH MADA - Hastangka Hastangka (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2014)
This article discusses the cosmological dimension of Universitas Gadjah Mada's Central Building (UCB) to explore the cosmological space in its architecture, how meaning of the space is constructed, and how the vertical and horizontal space division constructs its cosmological structure. The result of study found that the cosmological space dimension of the UCB consists of symbols which represent harmony and balance between the nature, human and God. The UCB was built based on the concept of abstract and symbolical space. The abstract space can be interpreted as a contextualization of harmonism values between human and nature. While the symbolical space can be interpreted as a contextualization of philosophical concept on imaginary line between Hinduism-Buddhism and Java. Relationship between religion and culture of Hinduism-Buddhism and Java had developed and influenced construction of the building. The UCB architecture contains dimension of macrocosm and micro- cosm space.